Editorial: Glial Plasticity in Depression - Oliveira, João F. (2016)
JO and LPreceived fellowships from the Foundation for Science and Technology (FCT)and their work is funded by FCT (SFRH/BD/101298/2014 to JO and IF/01079/2014 to LP) and Bial Foundation (207/14 for JO and 427/14 for LP) projects. SVis supported by FCT(SFRH/BPD/81627/2011).CG is supported by FCT(SFRH/BPD/63013/2009).This work wasco-funded by the Life and Health Sciences Research Institute (ICVS),and Northern Portugal Regional Operational Programme (NORTE2020), under the Portugal 2020 Partner ship Agreement, through the European Regional Development Fund (FEDER)(projects NORTE-01-0145-FEDER 000013 and NORTE-01-0145-FEDER- 000023).This work has been also funded by FEDER funds, through the Competitive ness Factors Operational Programme (COMPETE), and by National funds, through the (FCT), under the scope of the project POCI-01-0145-FEDER-007038.